2010
DOI: 10.1124/dmd.110.032755
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of [14C]BMS-690514 after Oral Administration to Rats, Rabbits, and Dogs

Abstract: ]BMS-690514 to rats and dogs, the majority of the radioactive dose (61-71%) was recovered in the feces, whereas 18 to 20% was eliminated in urine. In bile duct-cannulated rats, 83 and 17% of the administered radioactivity was recovered in the bile and urine, respectively, suggesting that biliary secretion was a major route for the elimination of BMS-690514-derived radioactivity in rats.The parent compound underwent extensive metabolism in both species, with <12% of the administered radioactivity recovered as B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…A similar type of condensation has been observed in the cytochrome P450-catalyzed oxidation and rearrangement of an amino pyrrolotriazine drug candidate (Fig. 30) [82]. …”
Section: Ring Formation Reactions As a Results Of Cytochrome P450 supporting
confidence: 68%
“…A similar type of condensation has been observed in the cytochrome P450-catalyzed oxidation and rearrangement of an amino pyrrolotriazine drug candidate (Fig. 30) [82]. …”
Section: Ring Formation Reactions As a Results Of Cytochrome P450 supporting
confidence: 68%
“…M1 was a prominent circulating metabolite found in the plasma of rats, rabbits, dogs, and humans after the administration of BMS-690514 , . M37, also present in these four species, was the precursor of a prominent O -glucuronide conjugate, M7 .…”
Section: Introductionmentioning
confidence: 97%
“…In vitro experiments suggested that direct glucuronidation and CYP2D6 and CYP3A4-mediated oxidation were likely to be important pathways in the metabolism of BMS-690514 . In vivo, BMS-690514 was well absorbed and highly metabolized in rats, dogs, and humans , . The primary metabolic pathways of this compound included hydroxylation, O -demethylation, and glucuronidation , (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations